MANAJEMEN WAKTU LANSIA PEMBELAJARAN MENGHAFAL AL-QUR’AN DI RUMAH QOUR’AN AT-TARTIL - Bici Jesni Ezani; Rufran Zulkarnain (UNIB Press, Universitas Bengkulu, 2021)
The purpose of this research is to find out and describe in detail the profile of an elderly woman aged 66 years who is a memorizer of the Al-Qur'an by following lessons at the Al-Qur'an At-Tartil House. This research is a qualitative descriptive research. This study uses interview data collection techniques, observation and documentation. Checking the validity of the data used time triangulation, subject triangulation and technical triangulation. The results of the research are that Grandma Arjuna, 66 years old, has memorized the Al-Qur'an by taking lessons at the Al-Qur'an At-Tartil House since 2013 and began memorizing in 2015. Achieved 7 juz memorization among 9 students in the Heaven's Angel class who is younger. Having a passion at the age of 66 to continue learning continuously which can illustrate the form of implementing the principle of lifelong education in the non-formal education pathway.